Information Asymmetry: Evidences about the Relationship between Auditor Tenure and Auditor Specialization - Shamsolah Shirinbakhsh; Zohreh Arefmanesh; Ameneh Bazrafshan (مطالعات تجربی حسابداری مالی, 2011)
Prior researches suggest that auditor specialization and auditor tenure increase audit quality and consequently improve quality of disclosed information and decrease information asymmetry. So the purpose of this paper is to examine the relationship between a company’s bid-ask spread, as a proxy of information asymmetry, and auditor tenure and specialization from 2002 to 2010 in the companies listed in Tehran Stock Exchange. Using regression analysis,the findings revealed that there is a negative and statistically significant relationship between auditor tenure and auditor specialization with information asymmetry. In other words auditor specialization and high auditor tenure decrease information asymmetry. In addition separating auditor tenure into short, medium and long periods confirmed the results too. Also the results show that the relationship between auditor tenure and information asymmetry is not influenced by selection of specialists or non-specialists.